(untitled) (International Journal of Engineering and Computer Science, 2014)
Enterprise Resource Planning is a business/technology term for an information system based on a common database and common application tools that allow real-time information to be accessed, shared and compared easily and immediately across organizations, agencies, divisions or departments. The objective of this application is to improve the administrative and operational functions by making them less complicated and more efficient. This, in turn, improves the ability to manage resources well and give better customer service. Basically it includes application modules for the CRM, Accounting, Taxation, Payroll, Inventory, HRMS and other important aspects of a business. This application is built on strong backend database My SQL Server. User management of Dhruval has multi-layer protection and hence users will be able to access data only to extent of privileges they have been given. Package also includes back up facility including auto backup facility.